USE OF AN ELISA ASSAY TO EVALUATE VENOM, ANTIVENOM, IgG AND IgM HUMAN ANTIBODY LEVELS IN SERUM AND CEREBROSPINAL FLUID FROM PATIENTS BITTEN BY Crotalus durissus terrificus IN BRAZIL - Barraviera, B. [UNESP]; Sartori, A. [UNESP]; Pereira Da Silva, M. F.; Kaneno, R. [UNESP]; Peraçoli, M. T. S. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1996)
A sandwich-type ELISA technique for specific and sensitive detection of Crotalus durissus terrificus venom antigens, horse-antivenom, human IgG and IgM antibodies was set up. Sixteen patients, 13 males and 3 females aged between 13 to 63 years (mean 33 ± 15) bitten by Crotalus durissus terrificus snakes were studied. Of the 15 patients, 6 had previously received anti-Crotalus venom and no seric venom was detected. For the other 9 patients studied, the venom levels ranged from 2 to 108 ng/ml according to the severity of each case. Seric antivenom was detected up to 44 days after the bite. IgM human antibody levels against Crotalus venom were higher between 3 and 18 days after specific treatment. IgG human antibody levels against Crotalus venom were detected between 30 and 90 days after envenoming. Venom and antivenom levels in cerebrospinal fluid were not observed 24 h after the bite. This suggests that neither the venom nor the antivenom is capable of crossing the blood-brain barrier. In addition, when either the venom or the antivenom is presented to the immune system cells an immune response is prepared.
Keywords: Enzyme-linked immunosorbent assay; Crotalus durissus terrificus; venom; antivenom; antibodies; cerebrospinal fluid